Disputing Citizenship - Clarke, John (Policy Press, 2014)
This unique book presents a new perspective on citizenship by treating it as a continuing focus of dispute. The authors develop a view of citizenship as always emerging from struggle through an exploration of the entanglements of politics, culture and power that are both embodied and contested in forms and practices of citizenship. This book will mainly appeal to scholars and students engaged by the question of citizenship, across a range of disciplines, as well as policymakers and practitioners.